Predictors of Professional Identity among Early Childhood Teacher Students - Anne Karin Vikstøl Olsen; Ingirid Geirsdatter Heald Kjær; Kristin Severinsen Spieler (MDPI AG, 2024)
Professional identity has been suggested to be decisive for efficiency and high work quality among the workforces. Central in early childhood teacher education is the development of students to become professional actors in a workplace setting upon graduation, thus developing a professional identity. However, the field lacks knowledge about the factors that are associated with professional identity among early childhood teacher students. Thereby, the aim of this study was to investigate the predictive value of learning climate (performance climate and mastery climate) in interaction with professors and academic self-efficacy on professional identity. The study adopted a quantitative cross-sectional approach, whereby data were collected by questionnaire. A total of 190 (first- and second-years students) attending a three-year bachelor's degree in early childhood teacher education completed the questionnaire. The results show that learning climate and academic self-efficacy are significantly associated with professional identity among early childhood teacher students, indicating the importance of facilitating a learning environment that promotes students' academic self-efficacy, mastery, and intellectual development. These findings indicate the importance of facilitating an environment that promotes students' academic self-efficacy, intellectual development, and a mastery-oriented climate, in addition to strengthening the connection and interaction between students and professors.